Histone Modifications and Chondrocyte Fate: Regulation and Therapeutic Implications - Wan, Chao; Zhang, Fengjie; Yao, Hanyu; Li, Haitao; Tuan, Rocky S. (Frontiers in Cell and Developmental Biology, 2021)
The involvement of histone modifications in cartilage development, pathology and regeneration is becoming increasingly evident. Understanding the molecular mechanisms and consequences of histone modification enzymes in cartilage development, homeostasis and pathology provides fundamental and precise perspectives to interpret the biological behavior of chondrocytes during skeletal development and the pathogenesis of various cartilage related diseases. Candidate molecules or drugs that target histone modifying proteins have shown promising therapeutic potential in the treatment of cartilage lesions associated with joint degeneration and other chondropathies. In this review, we summarized the advances in the understanding of histone modifications in the regulation of chondrocyte fate, cartilage development and pathology, particularly the molecular writers, erasers and readers involved. In addition, we have highlighted recent studies on the use of small molecules and drugs to manipulate histone signals to regulate chondrocyte functions or treat cartilage lesions, in particular osteoarthritis (OA), and discussed their potential therapeutic benefits and limitations in preventing articular cartilage degeneration or promoting its repair or regeneration.